Historizing Pre 9/11 Islamophobia in English Writings - Sadiya Abubakar; Zinah Fadhil Ali; Bilkisu Abubakar (Khazanah Pendidikan Islam, 2022)
Islamophobia is often explained as vile attitudes towards Muslims. Yet, Muslims are still labelled as bloodthirst.y terrorists, misogynists, or primitive in literature, media and academic or political discourses. These stereotypes have gone a long way in carving the image of Muslims globally, resulting to their marginalization, stigmatization or violently abused in some countries. Contrary to the general notion that Islamophobia developed after 9/11, this research argues that Islamophobia existed long before 9/11 in the form of stereotypical representations of Muslims. This study aims to briefly locate the earlier forms of Islamophobia through historical events like: pre-colonial encounters, series of wars and battles fought for the quest for empire expansion, unsuccessful or non-lasting colonialism, the postcolonial resistance and Muslims’ vicious reactions to anti-Islamic publications. The study interrogates the amplifications of stereotypes and persistent misrepresentations of Muslims which has long existed in traditional and modern English writings as a means of discerning and curbing the growth of Islamophobia. Homi Bhabha’s theory of stereotype will be used as the theoretical underpinning of this research. This study also looks at series of historical events of misrepresenting the Muslims in English writings and situates them within the Islamophobic implications that plague the world today.